2009
DOI: 10.1111/j.1749-6632.2009.04798.x
|View full text |Cite
|
Sign up to set email alerts
|

HE3286: A Novel Synthetic Steroid as an Oral Treatment for Autoimmune Disease

Abstract: HE3286 (17alpha-ethynyl-5-androstene-3beta, 7beta, 17beta-triol) is a synthetic derivative of a natural anti-inflammatory steroid, beta-AET (5-androstene-3beta, 7beta, 17beta-triol). HE3286 is orally bioavailable and treats established disease in models of ulcerative colitis, collagen-induced arthritis, and collagen antibody-induced arthritis, reducing clinical signs of disease and proinflammatory signals, including IL-6 and matrix metallopeptidase 3. HE3286 modulates nuclear factor kappaB through an unknown m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 26 publications
8
27
0
Order By: Relevance
“…In addition, we show herein that HE3286 was not immune suppressive in MLR studies and that extended pre-treatments were safe and may even have provided benefit in the murine model of myocarditis induced by CB3V infection. The present studies confirm the anti-inflammatory activity reported for HE3286 in our previous publications (23,24,26).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, we show herein that HE3286 was not immune suppressive in MLR studies and that extended pre-treatments were safe and may even have provided benefit in the murine model of myocarditis induced by CB3V infection. The present studies confirm the anti-inflammatory activity reported for HE3286 in our previous publications (23,24,26).…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies with AET showed benefit in rodent models of ulcerative colitis and multiple sclerosis (23,24). Thus, a broad based anti-inflammatory activity is perhaps central to the activities of HE3286 in auto-immune disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, the immunological effects of ␤AET in the PLN assay suggested Th2 promotion of antigen specific responses. These later observations are consistent with our previous reports that ␤AET treatment reduced disease in rodent models of experimental autoimmune encephalomyelitis [53] and TNBS-induced colitis [49]. In these models, reduced disease is often associated with an immune shift from a Th1/Th17 status to a Th2/regulatory T cell profile [54,55].…”
Section: Discussionsupporting
confidence: 90%
“…Qualitatively, the activity we observed was similar to DHEA [4], 5-androstenediol [27], and 17␣-alkynyl-␤AET [30,49] in chronic inflammation models. ␤AET's activity in RAW264.7 cells was similar to DHEA [50,51], although both DHEA and ␤AET were active only at 10 M, a concentration not readily achieved or sustained in vivo.…”
Section: Discussionsupporting
confidence: 64%